PLAGER-VG: platform for managing educational multiplayer video games - Padilla-Zea, Natalia; Medina Medina, Nuria; Gutiérrez Vela, Francisco L; Paderewski-Rodríguez, Patricia; Collazos, Cesar A (Multimedia Tools and Applications, 2017)
Information and communication technologies, in general, and multimedia systems, in particular, are currently incorporated into the learning processes with certain normality. Furthermore, the scientific community agrees that video games, as a specific expression of these technologies, present additional benefits that improve many student skills. In an educational context which uses video games as learning tools, the need for a well-defined framework to develop effective educational games seems evident. However, most educational games are not supported by specific architectures; perhaps because the existing ones do not include fundamental aspects such as collaboration, adaptation or gameplay, or its conceptual language is hardly understandable to the educational team. With the aim of fill this gap, we here describe the architecture PLAGER-VG to design, execute, monitor and adapt collaborative learning processes supported by video games, focusing the paper in the design and personalization aspects. PLAGER-VG is a modular platform composed of five sub-systems which allows incrementally designing video games and using them, as well as integrating a video game with other related to it. In particular, we propose the Design Sub-system for managing the educational game design process and the Personalization Sub-system for adapting the gameplay, and therefore the educational process, to the needs of students. The architecture has been considered during the development of several video games and a set of thirty teachers have expressed their acceptance regarding the main elements of PLAGER-VG.
Keywords: design of educational video games; architecture PLAGER-VG; collaborative learning; learning process personalization; JCR; Scopus